Efecto de la adición de ácidos orgánicos y probióticos sobre el crecimiento del camarón litopenaeus vannamei - González González, Yull Montgomery (2014)
This research was conducted in a shrimp located in the Palo Santo Island, Sabana Grande, parish Chongón, belonging to the canton Guayaquil, exhibition aimed to cultivate Litopenaeus vannamei in cages using organic acids and probiotics in feed. The use of fatty acids and probiotics in food is an alternative to improve the growth and survival of the species. For this reason in the present investigation the next target was raised: Determine the effect of adding organic acids plus a probiotic in the diet of white shrimp (Litopenaeus vannamei) to enhance their growth. Cultivated of shrimp held in cages at a density of 13 shrimps/m2, giving a total of 50 shrimp per cage. The abiotic control parameters was performed from day of cultivated for twelve weeks. The conclusions are: The culture was performed in cages L. vannamei for twelve weeks to test four feeding treatments, a control, one with organic acids, other organic acid + probiotics and finally one with probiotics, ANOVA statistical analysis indicates no significant difference among treatments for growth and survival end. However, the final biomass data suggest that treatment with probiotics was above all previous treatment with organic acids was higher than the control but inferior to probiotics. Feed conversion was lower in the probiotic treatment. Finally, the combination of organic acids and probiotics not provide better results compared to the individual use of probiotic.